The Application of Socioeducational Measures and the Recidivism of Those Who Left the Brasilian Socioeducational System (REMUNOM, 2024)
In front of the he high number of internals complying the social-educational measures provided in the Child and Adolescent Statute and the large number of repeat offenders in this social-educational system over the years, the question arises: The application of socio-educational measures may influence the recidivism of minors in conflit with law in criminality? The present work intends, per bibliographical research, to answer this question, exploring the socio-educational measures and the way in which they are applied in reality, combined with the search for data that reveals recidivism rates and the quantity of people complying with the measures. The article is divided into chapters that deal with the measures, their legal provisions, their characteristics, their inadequate application and the relationship with the hypothesis brought up in the work, the reduction of the age of criminal responsibility as a proposed solution and the ECA reforms.